American Cancer Society Head and Neck Cancer Survivorship Care Guideline. (22nd March 2016) - Cohen, Ezra E. W.; LaMonte, Samuel J.; Erb, Nicole L.; Beckman, Kerry L.; Sadeghi, Nader; Hutcheson, Katherine A.; Stubblefield, Michael D.; Abbott, Dennis M.; Fisher, Penelope S.; Stein, Kevin D.; Lyman, Gary H.; Pratt‐Chapman, Mandi L.
Abstract : Answer questions and earn CME/CNE The American Cancer Society Head and Neck Cancer Survivorship Care Guideline was developed to assist primary care clinicians and other health practitioners with the care of head and neck cancer survivors, including monitoring for recurrence, screening for second primary cancers, assessment and management of long‐term and late effects, health promotion, and care coordination. A systematic review of the literature was conducted using PubMed through April 2015, and a multidisciplinary expert workgroup with expertise in primary care, dentistry, surgical oncology, medical oncology, radiation oncology, clinical psychology, speech‐language pathology, physical medicine and rehabilitation, the patient perspective, and nursing was assembled. While the guideline is based on a systematic review of the current literature, most evidence is not sufficient to warrant a strong recommendation. Therefore, recommendations should be viewed as consensus‐based management strategies for assisting patients with physical and psychosocial effects of head and neck cancer and its treatment.CA Cancer J Clin 2016;66:203‐239. © 2016 American Cancer Society .